Simulation and experimental analysis of aerogel's attenuation for high-energy alpha particles in fission-fusion fragment rocket applications - Sandeep Puri; Andrew K. Gillespie; Ian Jones; Cuikun Lin; Ryan Weed; Robert V. Duncan (Nuclear Engineering and Technology)
Emerging studies are geared toward exploring new methods of nuclear rocket propulsion to provide more efficient space transit beyond Earth's orbit. One method is to employ a Fission Fragment Rocket Engine utilizing fissionable layers embedded in a low-density aerogel. A quantitative understanding of particle attenuation is essential for developing a functional prototype that permits fission fragments to escape the layers and contribute to specific impulse rather than being attenuated and generating waste heat. In this investigation, the MCNP code was used to theoretically analyze the attenuation of alpha particles from 241Am sources within aerogel materials. Simulations were conducted on aerogels with various densities and compositions. These simulations aimed to predict the expected intensity of alpha particles reaching a detector. CR-39 was employed as a Plastic Nuclear Track Detector to assess particle attenuation by the aerogels. The experimental and simulation results show that the threshold areal density of atoms was found to be high 1020 atoms/cm2 for the three materials studied in this project.